105k views
1 vote
(3 plus 3 a )plus (1 plus 5 m )(3 plus 3 a )plus (1 plus 5 m )equals nothing ​(Simplify your​ answer.)

User Carrabino
by
4.9k points

2 Answers

1 vote

I caculated it all and it is the same as Newton9022

Hope this helps.

User Roland Jegorov
by
4.4k points
1 vote

Answer:


7+6a+5m(4+3a)=0

Explanation:

We want to simplify the expression


(3 + 3 a ) + (1 + 5 m )(3 + 3 a ) + (1 + 5 m )=0

Expanding the expression in the middle


(3 + 3 a ) + 1 (3 + 3 a )+ 5 m (3 + 3 a ) + (1 + 5 m )=0

Eliminating all brackets


3 + 3 a + 3 + 3 a + 15m + 15m a + 1 + 5 m =0

Next, we collect our like terms


3+3+1+3a+3a+15m+5m+15ma=0

When you collect like terms, ensure the number of terms are still the same


7+6a+20m+15ma=0

This simplified gives us:


7+6a+5m(4+3a)=0

User TableCreek
by
5.3k points